# How do you multiply (5m-1)(6m-5)?

May 31, 2018

$30 {m}^{2} - 31 m + 5$

#### Explanation:

$\left(5 m - 1\right) \left(6 m - 5\right)$

= $5 m \left(6 m - 5\right) - 1 \left(6 m - 5\right)$

= $30 {m}^{2} - 25 m - 6 m + 5$

= $30 {m}^{2} - 31 m + 5$

May 31, 2018

$30 {m}^{2} - 31 m + 5$

#### Explanation:

$\left(5 m - 1\right) \left(6 m - 5\right)$

To multiply/simplify this, we use FOIL:

First, multiply out the $\textcolor{t e a l}{\text{firsts}}$:
$\textcolor{t e a l}{5 m \cdot 6 m = 30 {m}^{2}}$

Then the $\textcolor{\in \mathrm{di} g o}{\text{outers}}$:
$\textcolor{\in \mathrm{di} g o}{5 m \cdot - 5 = - 25 m}$

Now the $\textcolor{\mathrm{da} r k \mathmr{and} a n \ge}{\text{inners}}$:
$\textcolor{\mathrm{da} r k \mathmr{and} a n \ge}{- 1 \cdot 6 m = - 6 m}$

Finally the $\textcolor{f \mathmr{and} e s t g r e e n}{\text{lasts}}$:
$\textcolor{f \mathmr{and} e s t g r e e n}{- 1 \cdot - 5 = 5}$

Now combine them all together:
$\textcolor{t e a l}{30 {m}^{2}} \quad \textcolor{\in \mathrm{di} g o}{- \quad 25 m} \quad \textcolor{\mathrm{da} r k \mathmr{and} a n \ge}{- \quad 6 m} \quad \textcolor{f \mathmr{and} e s t g r e e n}{+ \quad 5}$

We can still combine the like terms $- 25 m - 6 m$:
$30 {m}^{2} - 31 m + 5$

Hope this helps!